Precision cut lung slices: an innovative tool for lung transplant research - Kollareth, Denny Joseph Manual; Sharma, Ashish K. (Frontiers in Immunology, 2024)
Lung ischemia-reperfusion injury (IRI), a common complication after lung transplantation (LTx), plays a crucial role in both primary graft dysfunction (PGD) and chronic lung allograft dysfunction (CLAD) thereby adversely impacting the clinical outcomes in these patient cohorts. Lung IRI is characterized by several molecular events including immune cell infiltration, reactive oxygen species (ROS) generation, calcium overload, inflammation and various forms of cell death pathways. Currently, no therapeutic agents are available to clinically prevent lung IRI. While animal and cell culture models are highly valuable in understanding the pathophysiology of lung IRI, they may not completely recapitulate the complexity of human lung tissue pathology. This limitation necessitates the requirement for developing innovative preclinical human research tools that can supplement available scientific modalities. Emerging evidence suggests that precision-cut lung slices (PCLS) have become an indispensable tool in scientific research to study lung biology in an ex vivo tissue system. Recent studies using PCLS have investigated lung diseases including asthma, chronic obstructive pulmonary disease (COPD), and lung cancer. Although PCLS can be successfully employed to determine the deleterious events in the pathogenesis of lung IRI, including cell-cell interactions as well as hallmarks of inflammation and oxidative stress-dependent pathways, detailed studies employing PCLS to decipher these molecular events in post-LTx injury are currently limited. This review focuses on the applicability and unexplored potential of PCLS as a powerful tool in lung IRI research for understanding the pathophysiology and consequent development of new therapeutic modalities.